Antibiotic stewardship benchmarking–Using the WHO point prevalence survey of antimicrobial prescribing in a Tertiary Care Public Hospital, Karachi - Ale Zehra; Tehreem Ansari; Syed Shaukat Ali Muttaqi Shah; Beenish Syed; Mehwish Rizvi; Fakhsheena Anjum; Tehrim Fatima; Farah Saeed (PLoS ONE, 2026)
Background Antimicrobial resistance (AMR) is a global threat, mainly linked to inappropriate use and prescription of antibiotics, Antimicrobial stewardship (AMS) programs have proved to promote responsible antibiotic use and decrease the burden of AMR. The aim of this study is to benchmark antibiotic prescribing patterns and evaluate stewardship practices using the World Health Organization (WHO) Point Prevalence Survey (PPS) methodology in a tertiary care public sector hospital in Karachi. Method A cross-sectional, prospective PPS was conducted over four weeks in July 2024 at Dow University Hospital, Karachi. The data were extracted from the medical records of the patients using a validated WHO PPS tool by a trained infectious disease physician and pharmacist. All inpatients admitted before or at 8:00 a.m. on survey day, without a planned discharge were included, excluding those from emergency, acute care, day-care surgery, dialysis, and oncology units. Descriptive analysis of the data was performed using Stata version 14. Results Out of 224 hospitalized patients at the day of survey, 186 inpatients (adults and children across medical, surgical and critical care wards) were included in the study meeting the inclusion criteria. The study included 50.5% male and 49.5% females, having mean age of 45 (±18) years. The point prevalence of antibiotic use was 83.3% (95% CI: 77.5–88.2%). Community-acquired infections 55.5% (95% CI: 48.7–62.1%) were the most common indication of use. Most antibiotics 99.2%, (95% CI: 95.6–99.9%) were prescribed empirically, with predominant parenteral administration 89.2% (95% CI: 84.5–92.9%) and limited Intravenous-to-oral switch 2.9% (95% CI: 1.3–6.2%). Ceftriaxone (18.5%), piperacillin-tazobactam (18.1%), and meropenem (16.2%) were most frequently used antibiotics. According to WHO Access, Watch and Reserve (AWaRe) classification, 80.8% (95% CI: 75.2–85.6%) of antibiotics belonged to the ‘Watch’ category, 17.3% (95% CI: 12.6–23.2%) to ‘Access’, and 1.8% (95% CI: 0.7–4.6%) to ‘ Reserve’. Cultures showed no growth in 64.8% (95% CI: 55.2–73.6%) of cases. Stewardship interventions were found applicable in 55.4% (95% CI: 48.7–62.0%) of prescriptions due to overuse, dosing errors, and absence of antimicrobial guideline in the hospitals. Conclusion This study demonstrates that antibiotic utilization exceeded global averages, highlighting the urgent need to develop institutional antimicrobial guidelines, enhance stewardship programs, and improve diagnostic stewardship to curb AMR.